2015
DOI: 10.11113/ijbes.v2.n4.94
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Morphology in the Form of Business Expansion: Perspective of Small Tourism Firm in Coastal Resort Destination

Abstract: Resort morphology literature can be traced back since 1930s and most cases referring to the coast of Europe and United State. In 1970s, it begins to give emphasis on aspects such as land use pattern, infrastructure, Central Business District, Recreational Business District and impact studies. The literature expands to the aspects of socioeconomic, hotel development and resort lifecycle in the 1980s. Later in 1990s, it was extended to politic and investment, tourist behavior, transportation, Tourism Business Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…Family firms are commercial organisations in which various generations of the same family influence the decision-making processes as well as the capacity to shape the visions and behaviours of companies and the will of the company in achieving its distinctive objectives (Lee et al , 2017; Mukarram et al , 2018; Panicker, 2017; Ye et al , 2019) and generally identified in the short term by means of the family leadership or ownership. For a company to classify as a family firm, there has to be a multi-generational and preponderant family dimension that ensures the unique dynamics and relationships ongoing in family firms (Chaudhary and Batra, 2018; Hussain and Ismail, 2015). There is common acceptance that the commitment of a family makes such businesses unique even while the literature continues to encounter certain difficulties in defining the actual behaviours of family-owned companies (der Heyden et al , 2005; Roy, 2016; Tsao et al , 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Family firms are commercial organisations in which various generations of the same family influence the decision-making processes as well as the capacity to shape the visions and behaviours of companies and the will of the company in achieving its distinctive objectives (Lee et al , 2017; Mukarram et al , 2018; Panicker, 2017; Ye et al , 2019) and generally identified in the short term by means of the family leadership or ownership. For a company to classify as a family firm, there has to be a multi-generational and preponderant family dimension that ensures the unique dynamics and relationships ongoing in family firms (Chaudhary and Batra, 2018; Hussain and Ismail, 2015). There is common acceptance that the commitment of a family makes such businesses unique even while the literature continues to encounter certain difficulties in defining the actual behaviours of family-owned companies (der Heyden et al , 2005; Roy, 2016; Tsao et al , 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%